Associations between Australian students’ literacy achievement in early secondary school and senior secondary participation in science: accessing cultural and science capital - Cooper, Grant; Thomas, Damon; Vaughan, Prain; Fraser, Sharon (Taylor & Francis, 2022)
ABSTRACT Introduction Factors affecting student pathways in senior secondary science The literacy factor in learning science Aim and research questions Method A Bourdieusian framing of capital and forms of science capital Results and discussion Conclusion Disclosure statement References Full Article Figures & data References Citations Metrics Reprints & Permissions PDF EPUB ABSTRACT Many factors are claimed to explain Australian students’ declining participation rates in senior secondary science subjects. These include, for instance, the influences of SES, indigeneity, and gender. While acknowledging the compelling case for these factors affecting student pathways, in this study we explore associations between students’ literacy achievement test scores in early secondary school and their senior secondary participation in science. Our analyses of Australian national literacy testing data indicated that students who subsequently studied physics, chemistry, and biology showed stronger foundational literacy competence than students not studying these subjects. Drawing on a Bourdieusian perspective, this research explores the conversion of cultural capital, in the form of language literacy achievement, into science capital. We consider that these findings (a) reconfirm the foundational role of literacy in all science learning, and (b) support a growing research agenda that focuses on how students can learn the particular literacies of science before senior secondary study. Our findings also have broader implications for policy and practices that support school student participation in science study.